Inhibitors of DNA repair and response to ionising radiation - Vischioni, B; Nicolay, N; Sharma, R; Helleday, T (2011)
Ionising radiation, and most chemotherapeutic agents currently used to treat cancer, target DNA to cause cytotoxicity. The cellular response to DNA damage is a complex set of intra-cellular processes involving multiple DNA repair pathways, leading either to cell death or to survival if the lesions are repaired or bypassed. Thus, the multiple and redundant pathways involved in the repair of DNA damage are important for therapeutic resistance. Within the past two decades the components of these DNA repair pathways have increasingly been investigated to generate new targeted drugs, which may be combined with conventional radiotherapy or DNA-damaging agents in the treatment of tumours. Furthermore, since many different types of human cancers arise from genetic or epigenetic mutations in proteins involved in DNA damage repair, over recent years targeted therapy approaches have been developed to utilise specific tumour-related DNA repair defects as monotherapy. This chapter gives an overview of the mechanisms involved in the repair of the lesions created by ionising radiation and provides details on the strategies that are currently under pre-clinical and clinical investigation to inhibit DNA repair pathways for potential therapeutic gain. © Springer Science+Business Media, LLC 2011.